2021
DOI: 10.1093/neuros/nyab164
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Growth Rate as a New Predictor of Progression-Free Survival After Chordoma Surgery

Abstract: BACKGROUND Currently, different postoperative predictors of chordoma recurrence have been identified. Tumor growth rate (TGR) is an image-based calculation that provides quantitative information of tumor's volume changing over time and has been shown to predict progression-free survival (PFS) in other tumor types. OBJECTIVE To explore the usefulness of TGR as a new preoperative radiological marker for chordoma recurrence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…For the intraspinal seeding metastasis in the C1-C2 region, surgical resection was the first choice and the patient still required intensive follow-up. Recently, Passeri et al ( 7 ) suggested tumor growth rate (TGR), showing the percentage change in tumor size over 1 month, may be considered as a preoperative radiological indicator of tumor proliferation and seems to preoperatively identify more aggressive tumors with a higher tendency to recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…For the intraspinal seeding metastasis in the C1-C2 region, surgical resection was the first choice and the patient still required intensive follow-up. Recently, Passeri et al ( 7 ) suggested tumor growth rate (TGR), showing the percentage change in tumor size over 1 month, may be considered as a preoperative radiological indicator of tumor proliferation and seems to preoperatively identify more aggressive tumors with a higher tendency to recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that whenever possible, total resection should be pursued ( 7 , 8 ). Chordoma in the sacrococcygeal region and other areas have a relatively high rate of total resection.…”
Section: Discussionmentioning
confidence: 99%
“…According to the methodology of a previous study, 17 Carestream R software (Carestream Health Inc) was used to semiautomatically quantify the volume of the tumor. In brief, the contours of the GCTB mass were manually traced at each imaging slice.…”
Section: Methodsmentioning
confidence: 99%